C.W. Mills' notion of the 'social milieu' and its relevance for contemporary society. (October 2022) - Jacobs, Keith; Malpas, Jeff
In Mills' sociological analysis, a central notion is the 'social milieu' which encapsulates 'the social setting of a person that is directly open to his personal experience'. For Mills, sociology should entail an investigation of the set of relations and practices that are a feature of human experience. Understanding the significance of Mills' approach, we argue, requires grasping the way the notion of 'milieu' or 'setting' itself draws upon spatial and topological notions – notions that have become prominent in much contemporary sociological thinking. From this perspective, Mills' work turns out to be relevant as a corrective, both to the undue emphasis on empirical particularity that is evident in some contemporary sociology and to what Mills viewed as 'abstract' theorisation. A large part of the relevance of Mills' work for contemporary sociological problems and challenges is thus to be found in the way his emphasis on situation (or 'place'), as given through the idea of 'milieu', allows a more complex and encompassing approach.